Managing International Human Resources At PT Garuda Indonesia - Jalaludin Rabbani; Iqbal Bagaswara; Muhammad Rayhan Yasser Nento; Sentot Imam Wahjono (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study examines the implementation of international human resource management (IHRM) practices at PT Garuda Indonesia in response to the evolving dynamics of the global aviation industry. The research explores how the company integrates digital transformation, global competence development, and organizational culture to enhance its competitiveness. The findings reveal that Garuda Indonesia has adopted several key strategies, including the digitalization of global recruitment, technology-based employee training, data-driven performance management, and the development of an international compensation system. These initiatives improve efficiency, transparency, and objectivity in decision-making while enabling the company to attract and retain high-quality global talent. Despite the extensive use of technology, Garuda Indonesia continues to maintain its distinctive Indonesian cultural values, such as hospitality and respect, as the foundation of its corporate identity. This cultural strength complements technological innovation, ensuring that digitalization enhances rather than diminishes the human touch in service delivery. Overall, the study concludes that effective international human resource management requires a balanced integration of technology, global competence, and organizational culture. Garuda Indonesia’s experience demonstrates how a national enterprise can successfully transform into a globally competitive organization while preserving its cultural authenticity.